Improvisasi Biogasolin pada Workshop Optimalisasi Kompetensi Otomotif Kelas XII SMK Bhakti Praja Adiwerna Tegal - Syarifudin Syarifudin; Faqih Fatkhurrozak; Firman Lukman Sanjaya; Eflita Yohana; Syaiful Syaiful; Muhammad Muhammad; Suhartana Suhartana (Universitas Muhammadiyah Semarang, 2025)
The largest contributors to unemployment are vocational high school graduates and Generation Z aged 15 to 24 years. This is contrary to the motto of vocational high schools as vocational schools prepare human resources equipped with Hard skills and Soft Skills as well as technological insight as needed by the business world and industry. Therefore, to reduce this phenomenon, grade XII students or prospective vocational high school alumni are given additional current insights and competency reviews through the Workshop on optimizing automotive competencies and developing Biogasoline fuel. The community service program aims to optimize automotive competencies in EFI-based fuel systems and provide insight into automotive developments regarding alternative Biogasoline fuels. The community service program students are 25 grade XII students of SMK majoring in Motorcycle Business Engineering where the department has wide job opportunities due to the development of motorized vehicles of the Motorcycle type. The methods applied are Workshops and case studies prepared through studies of EFI-based fuel systems and biogasoline as alternative fuels. The community service program was carried out on December 12 and 13, 2023 smoothly and successfully. Students' automotive competence in EFI-based fuel systems and insight into automotive technology developments in alternative gasoline fuels have been optimally achieved from 15.43% to 89.14%. The provision of workshop materials accompanied by demonstrations of automotive components accelerates students' understanding.